Pengaruh Ukuran Perusahaan, Pertumbuhan Aset, Keberwujudan Aset, Leverage, Dewan Direksi, dan Beban Penjualan Terhadap Kinerja Keuangan - Agnes Anggraini; Eny Purwaningsih (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to determine the results of the analysis of the influence of company size, asset growth, asset tangibility, leverage, board of directors, and sales expenses on the financial performance of companies operating in the food and beverage consumption industry sector that have been listed on the Indonesia Stock Exchange in the specified time period. starting from 2021-2023. By using a quantitative approach, this research succeeded in analyzing secondary data originating from 38 companies operating in the food and beverage consumption industry sector which have been declared to meet certain criteria. The results obtained from multiple linear regression analysis state that simultaneously, the six independent variables produce a significant influence on financial performance. Partially, company size and board of directors have a negative and significant influence on financial performance. Meanwhile, asset growth and asset tangibility have a positive and insignificant influence on financial performance. Leverage has an insignificant negative influence on financial performance. Meanwhile, sales expenses have a positive and significant influence on financial performance. The results obtained in this research reveal that operational strategies and resource management must be prioritized in order to achieve optimal financial performance in the consumption industry sector which operates in the food and beverage sector. It is hoped that carrying out this research can contribute to the literature regarding factors that can influence the financial performance of the food and beverage sector in Indonesia.